2015
DOI: 10.1159/000369735
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthyroidism Evokes Myocardial Ceramide Accumulation

Abstract: Background: Thyroid hormones (THs) are key regulators of cardiac physiology as well as modulators of different cellular signals including the sphingomyelin/ceramide pathway. The objective of this study was to examine the effect of hyperthyroidism on the metabolism of sphingolipids in the muscle heart. Methods: Male Wistar rats were treated for 10 days with triiodothyronine (T3) at a dose of 50µg/100g of body weight. Animals were then anaesthetized and samples of the left ventricle were excised. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…Prolonged treatment with T 3 led to a prominent increase of DHS, sphingosine, ceramide and SM levels, but decreased S1P levels, in cardiomyocytes taken from the LV of male mice. 66 Consistent with this, data demonstrated that T 3 treatment reduced the activity of nSMase, but caused no change in ceramidase activity, which would be required to generate sphingosine as a substrate for SphKs. 66 …”
Section: Sphingolipids In Secondary Cardiomyopathiessupporting
confidence: 69%
See 1 more Smart Citation
“…Prolonged treatment with T 3 led to a prominent increase of DHS, sphingosine, ceramide and SM levels, but decreased S1P levels, in cardiomyocytes taken from the LV of male mice. 66 Consistent with this, data demonstrated that T 3 treatment reduced the activity of nSMase, but caused no change in ceramidase activity, which would be required to generate sphingosine as a substrate for SphKs. 66 …”
Section: Sphingolipids In Secondary Cardiomyopathiessupporting
confidence: 69%
“… 66 Consistent with this, data demonstrated that T 3 treatment reduced the activity of nSMase, but caused no change in ceramidase activity, which would be required to generate sphingosine as a substrate for SphKs. 66 …”
Section: Sphingolipids In Secondary Cardiomyopathiessupporting
confidence: 69%
“…Routine Western blotting procedures were used to detect protein content as described previously [ 38 40 ]. The samples were homogenized in ice-cold RIPA (radioimmunoprecipitation assay) buffer (50 mM Tris-HCl, 150 M NaCl, 1 mM EDTA, 1% NP-40, 0.25% Na-deoxycholate, 1 mM phenylmethylsulfonyl fluoride, 1 μ g/ml aprotinin, 1 μ g/ml leupeptin, 1 μ g/ml pepstatin, 1 mM sodium orthovanadate, and 1 mM sodium fluoride) for 1 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…A variety of sphingolipids were derived from the sphingosine backbone (21). Sphingosine itself also plays a unique role in the formation of 1-sphingosine (S1P), which is a marker of atherosclerosis after binding to HDL-C (22). Sphingosine and its derivatives play a role to prevent a variety of lipid deposition, vascular intimal focal fibrosis after combination with HDL-C (23).…”
Section: Discussionmentioning
confidence: 99%